The making of technique in the arts theories and practice from the sixteenth to the twentieth century - Dupré, Sven 1975-; Hendriksen, Marieke M. A. 1982- (Brepols, 2023)
"What is technique in the arts? Now widely used to refer to the practical aspects of art making, 'technique' was a neologism in the vernacular, and started to appear in treatises on arts and sciences from around 1750. Rooted in the Greek "techne?", which was translated routinely as ?art? until the mid-eighteenth century, technique referred to processes of making or doing and their products. Described previously as ?art?, ?methods?, ?manners? or ?mechanics?, techniques were recorded in text with the intention of documenting or transmitting practical skills and knowledge. This book bridges the gap between the changing concept of technique and the practices currently described by it. It explores the linguistic, philosophical, and pedagogic history of technique in the arts, answering the question why the term ?technique? first emerged around 1750, and exploring how its meaning to artists, art theorists, and natural philosophers changed until the twentieth century."
Acknowledgements: "This book results from two workshops on 'The Making of Technique' held at Utrecht University in October 2017 and March 2019."
Keywords: Geschichte 1500-2000; Theorie; Kunst; Künstlerische Technik; Konferenzschrift -- Utrecht University -- 10.2017 -- Utrecht; Konferenzschrift -- Utrecht University -- 03.2019 -- Utrecht